Response of Australian Summer Monsoon Precipitation to a Strengthening Antarctic Circumpolar Current - Yuhui Han; Song Yang; Peixi Wang; Zhenning Li; Xiaoming Hu (Geophysical Research Letters)
Abstract The Australian summer monsoon (AUSM) is the strongest monsoon in the Southern Hemisphere and it is greatly influenced by the climate conditions in the Indo‐Pacific and adjacent regions. Inspite of the substantial studies of the monsoon, the linkage between the AUSM and the high‐latitude Southern Ocean climate has not been fully understood. This study investigates how AUSM rainfall is affected by the Antarctic Circumpolar Current (ACC) by simulating scenarios with a closed and an opened Drake Passage with the Community Earth System Model. It is found that AUSM precipitation decreases as a result of reduced local humidity caused by a strengthening ACC. An opened Drake Passage leads to strengthening ACC and Atlantic Meridional Overturning Circulation, which in turn creates an El Niño‐like state in the Pacific. This weakens the Walker Circulation, resulting in reduced local moisture, anomalous subsidence over the AUSM region, and a subsequent decrease in monsoon precipitation.